A review of virus host factor discovery using CRISPR screening - Wayne Ren See; Meisam Yousefi; Yaw Shin Ooi (mBio)
ABSTRACT The emergence of genome-scale forward genetic screening techniques, such as Haploid Genetic screen and clustered regularly interspaced short palindromic repeats (CRISPR) knockout screen has opened new horizons in our understanding of virus infection biology. CRISPR screening has become a popular tool for the discovery of novel host factors for several viruses due to its specificity and efficiency in genome editing. Here, we review how CRISPR screening has revolutionized our understanding of virus-host interactions from scientific and technological viewpoints. A summary of the published screens conducted thus far to uncover virus host factors is presented, highlighting their experimental design and significant findings. We will outline relevant methods for customizing the CRISPR screening process to answer more specific hypotheses and compile a glossary of conducted CRISPR screens to show their design aspects. Furthermore, using flaviviruses and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) as examples, we hope to offer a broad-based perspective on the capabilities of CRISPR screening to serve as a reference point to guide future unbiased discovery of virus host factors.